Analisis Pengaruh Teknologi Informasi Terhadap Kinerja Karyawan Pada Departemen Kualitas di PT Gelindo Garmentama - Selly Yulianty; Lies Anggi Puspita Dewi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2024)
This study aims to determine the effect of information technology on employee performance. This study focuses on examining the effect of information technology on employee performance in the quality department at PT Gelindo Garmentama. The data collected in this study is through distributing questionnaires to all employees in the Quality Department who are directly affected by the use of information technology and are thoroughly sampled. The author will analyze data such as the system used and system users. The author analyzes the data using a simple linear regression test to prove the influence between information technology on employee performance. Based on the research results, information technology significantly affects employee performance in the Quality Department at PT Gelindo Garmentama Keywords: Information Technology, Employee Performance, Quality Deppartment